EKSTERNAL DAN INTERNAL DALAM MENENTUKAN NON PERFORMING FINANCING PADA PERBANKAN SYARIAH - Ratna; Pani Akhiruddin Siregar (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2018)
This research aims to analyze the extent of the influence of the exchange rate, inflation, and CAR against FDR NPF Islamic banking in Indonesia. Approach to research with quantitative methods using secondary data. Types of quantitative data in the form of data runtun time (time series) monthly Statistics sourced from Bank Indonesia Sharia Banking/financial service Authority (SPS-BI/OJK) from January 2006 until January 2018. Research models elaborated in the equation a linear multiple regression analysis with 0,05 significance level. Test results of F, free variables (Exchange rates, inflation, CAR and FDR) simultaneously significantly affect a bound variable (NPF). This indicates that the regression model on exchange rate, inflation, CAR and FDR could be used to predict the NPF. Whose hypotheses there is significant influence among variables a variable is bound against free. From the results of the test t, variable rate and variable inflation partially positive and significant influential variable against the NPF. However, variables and variable FDR CAR partially positive and no significant effect against the NPF variable. From the results of the estimation model, the retrieved value R of the determination coefficient R 0,532 and the Square of the mean 0,283 of 28,30% of the variation could be explained by the bound variables are variables in the model. While the rest of 71,70% explained by other causes which are not entered into the model.